Flux composition, solder composition, electronic substrate, and method for manufacturing electronic substrate

By using a flux composition of polyalkylene glycol fatty acid ester and polyglycerol fatty acid ester with an HLB value greater than 10 and a freezing point below 35°C and triethylene glycol monobutyl ether, the problems of cleaning and printing properties of post-soldering residues are solved, and excellent welding effects are achieved.

CN120644861APending Publication Date: 2025-09-16TAMURA KK
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510288595.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-14
Filing Date
2025-03-12
Publication Date
2025-09-16

AI Technical Summary

Technical Problem

The existing solder compositions have poor cleaning and printability of the residues after soldering. Especially after using aqueous cleaning agents, the cleaning property of the flux residues becomes worse, which affects the soldering quality.

Method used

The invention adopts polyalkylene glycol fatty acid ester and polyglycerol fatty acid ester with HLB value greater than 10 and freezing point below 35°C as resin components, combines triethylene glycol monobutyl ether as solvent, and adds appropriate amount of activator and solder powder to form a flux composition.

Benefits of technology

The excellent cleaning and printing properties of flux residues based on water-based cleaning agents are achieved, ensuring the welding quality and reducing the adverse effects of flux residues on the welding process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005307881150000131
    Figure BDA0005307881150000131
Patent Text Reader

Abstract

A flux composition containing (A) a resin, (B) an activator, and (C) a solvent, the component (A) being at least one selected from the group consisting of polyalkylene glycol fatty acid esters and polyglycerol fatty acid esters and having an HLB value of more than 10 and a freezing point of 35 DEG C or less, and the component (C) containing (C1) triethylene glycol monobutyl ether.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a flux composition, a solder composition and an electronic substrate. Background Art

[0002] The solder composition is a paste-like mixture obtained by kneading a flux composition (rosin-based resin, activator, solvent, etc.) and solder powder (see Document 1: Japanese Patent No. 5887330).

[0003] When soldering with a solder composition, flux residue remains around the joint after soldering. This residue contains activator components, among other things, and there is a risk of moisture intruding into the residue due to condensation, causing ion migration. This residue is distributed across the electrodes. Furthermore, the presence of flux residue on the surface can sometimes cause problems during the molding or coating process, or lead to poor bonding during wire bonding. Therefore, it is desirable to remove this residue by cleaning after bonding.

[0004] Conventionally, cleaning methods have been used that use cleaning agents containing high-cleaning power organic solvents as their main component. However, due to the high content of solvents, restrictions have been tightened from the perspectives of preventing water pollution, fire and air pollution, as well as from the perspective of production hygiene.

[0005] Therefore, in recent years, the use of water-based cleaning agents has been reduced, with the use of water as the main component. Furthermore, there is a demand for the use of water as a cleaning agent. Consequently, changes in cleaning agent composition have led to a tendency for flux residue cleaning performance to deteriorate, which has become a problem.

[0006] Furthermore, if components that are easily soluble in water are used as components of the flux composition, the paste properties may be deteriorated due to moisture absorption, precipitation of some components, and the like, and the printability of the solder composition may tend to be deteriorated. Summary of the Invention

[0007] An object of the present invention is to provide a flux composition, a solder composition, and an electronic substrate that are excellent in cleaning properties of flux residues with an aqueous cleaning agent and excellent in printability.

[0008] According to the present invention, the following flux composition, solder composition, and electronic substrate can be provided.

[0009] [1] A flux composition comprising (A) a resin, (B) an activator, and (C) a solvent,

[0010] The component (A) has an HLB value greater than 10 and a freezing point of 35°C or less, and is at least one selected from polyalkylene glycol fatty acid esters and polyglycerol fatty acid esters.

[0011] The component (C) contains (C1) triethylene glycol monobutyl ether.

[0012] [2] The flux composition according to [1], wherein

[0013] The component (C) further contains (C2) triethylene glycol monoethyl ether.

[0014] [3] The flux composition according to [1] or [2], wherein

[0015] The component (B) contains (B1) an organic acid and (B3) an amine activator.

[0016] [4] A solder composition comprising the flux composition according to any one of [1] to [3] and (D) solder powder.

[0017] [5] An electronic substrate having a soldered portion using the solder composition described in [4].

[0018] According to one embodiment of the present invention, a flux composition, a solder composition, and an electronic substrate can be provided that are excellent in cleaning properties of flux residues with an aqueous cleaning agent and excellent in printability. DETAILED DESCRIPTION

[0019] [Flux composition]

[0020] First, the flux composition of this embodiment will be described. The flux composition of this embodiment comprises, in addition to solder powder, the following components: (A) a resin, (B) an activator, and (C) a solvent. Component (A) has an HLB value greater than 10 and a freezing point of 35°C or less, and is at least one selected from polyalkylene glycol fatty acid esters and polyglycerol fatty acid esters. Component (C) contains (C1) triethylene glycol monobutyl ether.

[0021] According to this embodiment, a flux composition having excellent cleaning properties for flux residues using an aqueous cleaning agent and excellent printability can be obtained. The reason for this is not yet clear, but the present inventors speculate as follows.

[0022] That is, in this embodiment, at least one selected from polyalkylene glycol fatty acid esters and polyglycerol fatty acid esters having an HLB value greater than 10 and a freezing point of 35°C or less is used as the (A) resin. This (A) component is a component that is easily soluble in water, and therefore can improve the cleaning properties of flux residues based on aqueous cleaning agents. On the other hand, the (A) component is prone to problems such as moisture absorption and is a component that may have an adverse effect on printability. However, surprisingly, by using this (A) component in combination with (C1) triethylene glycol monobutyl ether, the adverse effect on printability can be suppressed. As described above, the present inventors speculate that the above-mentioned effects of the present invention can be achieved thereby.

[0023] [(A) ingredient]

[0024] The resin (A) used in this embodiment is at least one selected from polyalkylene glycol fatty acid esters and polyglycerol fatty acid esters having an HLB value greater than 10 and a freezing point of 35° C. or less. These may be used alone or in combination of two or more.

[0025] When the HLB value of component (A) is 10 or less, the cleaning performance of flux residue becomes insufficient. From the same viewpoint, the HLB value of component (A) is preferably 10.2 or more and 18 or less, and more preferably 10.4 or more and 16 or less.

[0026] If the freezing point of component (A) exceeds 35°C, the cleaning properties of flux residues become insufficient. From the same viewpoint, the freezing point of component (A) is preferably 30°C or lower, more preferably 25°C or lower, and particularly preferably 20°C or lower. The freezing point can be measured, for example, by the method described in JIS K0065.

[0027] Component (A) includes tetraglycerol monolaurate (HLB value 10.4, freezing point 20°C or lower), hexaglycerol monoisostearate (HLB value 10.8, freezing point 20°C or lower), hexaglycerol monooleate (HLB value 11.6, freezing point 20°C or lower), decaglycerol monolaurate (HLB value 14.7, freezing point 20°C or lower), and polyoxyethylene monostearate (HLB value 11.6, freezing point 35°C).

[0028] The amount of component (A) added relative to 100 mass% of the flux composition is preferably 20 mass% to 50 mass%, more preferably 25 mass% to 40 mass%. When the amount of component (A) is at least the lower limit, its function as a binder component can be ensured. Furthermore, when the amount of component (A) is at most the upper limit, its adverse effect on printability is sufficiently minimal.

[0029] [(B) ingredient]

[0030] Examples of the activator (B) used in this embodiment include (B1) an organic acid, (B2) a halogen-based activator, and (B3) an amine-based activator. These activators may be used alone or in combination of two or more. From the perspective of activation, it is preferred to use (B1) an organic acid and (B3) an amine-based activator in combination. It should be noted that (B2) a halogen-based activator may also be used in combination.

[0031] As the component (B1), other organic acids may be mentioned in addition to monocarboxylic acids, dicarboxylic acids, and the like.

[0032] Examples of the monocarboxylic acid include formic acid, acetic acid, propionic acid, butyric acid, valeric acid, hexanoic acid, heptanoic acid, decanoic acid, lauric acid, myristic acid, pentadecanoic acid, palmitic acid, heptadecanoic acid, stearic acid, tuberostearic acid, arachidic acid, behenic acid, lignoceric acid, and glycolic acid.

[0033] Examples of the dicarboxylic acid include oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, fumaric acid, maleic acid, tartaric acid, and diglycolic acid.

[0034] Examples of other organic acids include dimer acid, trimer acid, levulinic acid, lactic acid, acrylic acid, benzoic acid, salicylic acid, anisic acid, citric acid, and picolinic acid.

[0035] The amount of component (B1) blended relative to 100 mass% of the flux composition is preferably 0.1 mass% to 5 mass%, more preferably 0.5 mass% to 4 mass%. When the amount of component (B1) blended is at least the lower limit, solderability tends to be improved; on the other hand, when it is at most the upper limit, the insulating properties of the flux composition tend to be maintained.

[0036] Examples of the component (B2) include halogenated alcohols and halogenated carboxylic acid compounds.

[0037] Examples of the halohydrin include bromohydrins such as 2,3-dibromopropanol, 2,3-dibromobutanediol, trans-2,3-dibromo-2-butene-1,4-diol, 1,4-dibromo-2-butanol, and tribromoneopentyl alcohol; chlorohydrins such as 1,3-dichloro-2-propanol and 1,4-dichloro-2-butanol; fluorohydrins such as 3-fluorocatechol; and other similar compounds.

[0038] Examples of the halogenated carboxylic acid compound include iodinated carboxylic acid compounds such as 2-iodobenzoic acid, 3-iodobenzoic acid, 2-iodopropionic acid, 5-iodosalicylic acid, and 5-iodoanthranilic acid; chlorocarboxylic acid compounds such as 2-chlorobenzoic acid and 3-chloropropionic acid; bromocarboxylic acid compounds such as 2,3-dibromopropionic acid, 2,3-dibromosuccinic acid, and 2-bromobenzoic acid; and other similar compounds.

[0039] When component (B2) is used, its blending amount is preferably from 0.1% to 5% by mass, more preferably from 0.5% to 4% by mass, relative to 100% by mass of the flux composition. When the blending amount of component (B2) is above the lower limit, solderability tends to be improved. On the other hand, when it is below the upper limit, it is preferred from the perspective of halogen-free addition to the solder composition.

[0040] Component (B3) includes N,N,N',N'-tetrakis(2-hydroxypropyl)ethylenediamine and N,N,N',N'-tetrakis(2-hydroxyethyl)ethylenediamine. Of these, N,N,N',N'-tetrakis(2-hydroxypropyl)ethylenediamine is preferred from the viewpoint of improving solder wettability.

[0041] The amount of component (B3) blended relative to 100 mass% of the flux composition is preferably 0.1 mass% to 20 mass%, more preferably 1 mass% to 15 mass%, and particularly preferably 5 mass% to 12 mass%. When the amount of component (B3) blended is at least the lower limit, solderability tends to be improved. On the other hand, when it is at most the upper limit, the storage stability of the flux composition tends to be maintained.

[0042] The amount of component (B) blended relative to 100 mass% of the flux composition is preferably 1 mass% to 25 mass%, more preferably 3 mass% to 20 mass%, and particularly preferably 5 mass% to 18 mass%. When the amount of component (B) blended is at least the lower limit, the activation effect tends to be enhanced. On the other hand, when it is at most the upper limit, the insulating properties of the flux composition tend to be maintained.

[0043] [(C) ingredient]

[0044] The solvent (C) used in this embodiment must contain (C1) triethylene glycol monobutyl ether (melting point -48°C, boiling point 271°C). Component (C1) maintains the printability of the solder composition even when component (A) is used. It should be noted that, in this specification, the boiling point refers to the boiling point at 1013 hPa.

[0045] The amount of component (C1) added relative to 100% by mass of the flux composition is preferably 10% to 50% by mass, more preferably 15% to 45% by mass, and particularly preferably 20% to 40% by mass. When the amount of component (C1) is at least the lower limit, the printability of the solder composition can be further improved. On the other hand, when the amount of component (C1) is at most the upper limit, adverse effects on other properties are minimal.

[0046] The component (C) preferably further contains (C2) triethylene glycol monoethyl ether (melting point -44°C or lower, boiling point 249°C). The component (C2) can further improve the printability of the solder composition.

[0047] When component (C2) is used, its amount is preferably from 5% to 30% by mass, more preferably from 8% to 25% by mass, and particularly preferably from 12% to 20% by mass, relative to 100% by mass of the flux composition. When the amount of component (C2) is within this range, the printability of the solder composition can be further improved without degrading other physical properties.

[0048] The component (C) may contain a solvent (component (C3)) other than the component (C1) and the component (C2) as long as the object of the present invention can be achieved.

[0049] Component (C3) includes diethylene glycol monohexyl ether (DEH, melting point -40°C, boiling point 259°C), 1,4-butanediol (melting point 19°C, boiling point 228°C), 1,6-hexanediol (melting point 42°C, boiling point 250°C), 2,2-dimethyl-1,3-propanediol (melting point 128°C, boiling point 210°C), and 2,5-dimethyl-2,5-hexanediol (melting point 89°C, boiling point 214°C). These may be used alone or in combination of two or more.

[0050] The total amount of components (C1) and (C2) is preferably 70% by mass or more, more preferably 80% by mass or more, and particularly preferably 90% by mass or more relative to 100% by mass of component (C).

[0051] The amount of component (C) relative to 100 mass% of the flux composition is preferably 10 mass% to 70 mass%, more preferably 20 mass% to 65 mass%, and particularly preferably 30 mass% to 60 mass%. When the amount of the solvent is within the above range, the viscosity of the resulting solder composition can be appropriately adjusted to a reasonable range.

[0052] [Thixotropic agent]

[0053] From the perspective of suppressing sag during printing or heating, the flux composition of this embodiment may further contain a thixotropic agent. Known thixotropic agents can be used as appropriate. Examples of thixotropic agents include solidified castor oil, amides, kaolin, colloidal silica, organobentonite, and glass powder. Among these, amides are preferred from the perspective of suppressing sag. These may be used alone or in combination of two or more.

[0054] When a thixotropic agent is used, its amount is preferably from 2% to 20% by mass, more preferably from 3% to 15% by mass, relative to 100% by mass of the flux composition. When the amount is above the lower limit, sufficient thixotropy is achieved, and sag tends to be suppressed. On the other hand, when the amount is below the upper limit, the thixotropy does not become excessively high, and printing defects tend to be less likely to occur.

[0055] [Antioxidants]

[0056] From the perspective of solder meltability, the flux composition of this embodiment may further contain an antioxidant. Known antioxidants can be used as appropriate. Examples of antioxidants include sulfur compounds, hindered phenol compounds, and phosphite compounds. Hindered phenol compounds are preferred.

[0057] Examples of the hindered phenol compound include pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], ethylene bis(oxyethylene)bis(3-tert-butyl-4-hydroxy-5-methylphenylpropionate), N,N'-bis[2-[2-(3,5-di-tert-butyl-4-hydroxyphenyl)ethylcarbonyloxy]ethyl]oxamide, and N,N'-bis{3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl}hydrazine.

[0058] When an antioxidant is used, the amount thereof is preferably from 0.1% to 5% by mass relative to 100% by mass of the flux composition. When the amount of the antioxidant is above the lower limit, the solder meltability tends to be improved. On the other hand, when it is below the upper limit, the insulating properties of the flux composition tend to be maintained.

[0059] [Other ingredients]

[0060] The flux composition used in this embodiment may contain other additives as needed, in addition to component (A), component (B), component (C), a thixotropic agent, and an antioxidant. Examples of other additives include imidazole compounds, defoaming agents, modifiers, matting agents, and foaming agents. The amount of these additives added is preferably 0.01% to 5% by mass relative to 100% by mass of the flux composition.

[0061] [Solder composition]

[0062] Next, the solder composition of this embodiment will be described. The solder composition of this embodiment contains the flux composition of this embodiment described above and (D) solder powder described below.

[0063] The amount of the flux composition added relative to 100% by mass of the solder composition is preferably 5% by mass or more and 35% by mass or less, more preferably 7% by mass or more and 20% by mass or less, and particularly preferably 8% by mass or more and 15% by mass or less. If the amount of the flux composition added is less than 5% by mass (if the amount of solder powder added exceeds 95% by mass), the flux composition as a binder is insufficient, and thus mixing the flux composition and solder powder tends to be difficult. On the other hand, if the amount of the flux composition added exceeds 35% by mass (if the amount of solder powder added is less than 65% by mass), it tends to be difficult to form a sufficient solder joint when the resulting solder composition is used.

[0064] [(D) ingredient]

[0065] The solder powder (D) used in this embodiment is preferably composed solely of lead-free solder powder, but may also be lead-containing solder powder. Furthermore, the solder alloy in the solder powder preferably contains at least one selected from the group consisting of tin (Sn), copper (Cu), zinc (Zn), silver (Ag), antimony (Sb), lead (Pb), indium (In), bismuth (Bi), nickel (Ni), cobalt (Co), and germanium (Ge).

[0066] The solder alloy in the solder powder is preferably an alloy containing tin as a main component. Furthermore, the solder alloy more preferably contains tin, silver, and copper. Furthermore, the solder alloy may contain at least one of antimony, bismuth, and nickel as an additive element.

[0067] Here, the term "lead-free solder powder" refers to a powder of a solder metal or alloy to which no lead is added. However, lead is allowed to exist as an unavoidable impurity in the lead-free solder powder. In this case, the amount of lead is preferably 300 ppm by mass or less.

[0068] Specific examples of lead-free solder powder alloy systems include Sn-Ag-Cu, Sn-Cu, Sn-Ag, Sn-Bi, Sn-Ag-Bi, Sn-Ag-Cu-Bi, Sn-Ag-Cu-Ni, Sn-Ag-Cu-Bi-Sb, Sn-Ag-Bi-In, and Sn-Ag-Cu-Bi-In-Sb.

[0069] The average particle size of component (D) is generally 1 μm to 40 μm, and is more preferably 1 μm to 35 μm, further preferably 2 μm to 35 μm, and particularly preferably 3 μm to 32 μm, from the perspective of being able to cope with electronic substrates with narrow pad spacing. It should be noted that the average particle size can be measured using a dynamic light scattering particle size analyzer.

[0070] [Method for producing solder composition]

[0071] The solder composition of the present embodiment can be produced by mixing the flux composition described above and the (D) solder powder described above in the above-described ratio and stirring and mixing them.

[0072] [Electronic substrate]

[0073] Next, the electronic substrate of the present embodiment is described. The electronic substrate of the present embodiment is characterized in that it has a soldering portion using the solder composition of the present embodiment. The electronic substrate of the present embodiment can be manufactured by mounting electronic components on an electronic substrate (printed wiring board, etc.) using the solder composition.

[0074] Examples of the coating apparatus used here include a screen printer, a metal mask printer, a dispenser, and a jet dispenser.

[0075] Furthermore, electronic components can be mounted on electronic substrates through a reflow process in which electronic components are placed on a solder composition applied by a coating device and heated in a reflow oven under predetermined conditions to thereby mount the electronic components on a printed wiring board.

[0076] In the reflow process, electronic components are placed on a solder composition and heated in a reflow oven under predetermined conditions. This reflow process allows for a sufficient solder joint to be formed between the electronic components and the printed wiring board. As a result, the electronic components can be mounted on the printed wiring board.

[0077] The reflow conditions can be appropriately set according to the melting point of the solder. For example, the preheating temperature is preferably 140°C to 200°C, more preferably 150°C to 160°C. The preheating time is preferably 60 seconds to 120 seconds. The peak temperature is preferably 230°C to 270°C, more preferably 240°C to 255°C. In addition, the holding time at a temperature of 220°C or higher is preferably 20 seconds to 60 seconds.

[0078] After the reflow process, it is preferable to perform a cleaning process of cleaning flux residue on the electronic substrate using an aqueous cleaning agent.

[0079] As a cleaning method, an immersion method, a jet method, etc. can be used.

[0080] For example, in the immersion method, the electronic substrate can be immersed in an aqueous cleaning agent. It should be noted that ultrasonic waves can also be applied at this time.

[0081] As an aqueous cleaning agent, a known aqueous flux residue cleaning agent can be used. Here, aqueous means containing water as the main component (water accounting for 50% or more by mass). Commercially available products include "VIGONUS" manufactured by Zestron Japan and "Pine Alpha ST-180K" manufactured by Arakawa Chemical Industries, Ltd.

[0082] Furthermore, from an environmental perspective, the aqueous cleaning agent is preferably water.

[0083] The temperature of the aqueous cleaning agent during cleaning is, for example, 20° C. or higher and 70° C. or lower.

[0084] The cleaning time is, for example, not less than 1 minute and not more than 10 minutes.

[0085] Rinsing can be performed after cleaning with an aqueous detergent. Rinsing conditions are not particularly limited, and can be performed using water at 20°C to 50°C for approximately 0.5 to 5 minutes. Rinsing can be performed two or more times.

[0086] The flux composition, solder composition, and electronic substrate of the present embodiment are not limited to the above-described embodiment, and the present invention also includes modifications, improvements, and the like within the scope of achieving the object of the present invention.

[0087] For example, for the above-mentioned electronic substrate, the printed wiring board and the electronic components are joined together by a reflow soldering process, but are not limited thereto. For example, the printed wiring board and the electronic components can be joined together by a process (laser heating process) in which a solder composition is heated using a laser instead of the reflow soldering process. In this case, the laser light source is not particularly limited and can be appropriately adopted according to the wavelength that meets the metal absorption band. As the laser light source, for example: solid laser (ruby, glass, YAG, etc.), semiconductor laser (GaAs and InGaAsP, etc.), liquid laser (pigment, etc.) and gas laser (He-Ne, Ar and CO2, excimer, etc.) can be cited.

[0088] Example

[0089] Next, the present invention will be described in further detail with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples. Note that the materials used in the Examples and Comparative Examples are shown below.

[0090] ((A) ingredient)

[0091] Polyglycerol fatty acid ester A: Tetraglycerol monolaurate (HLB value 10.4, freezing point 20°C or less), trade name "ML-310", manufactured by Sakamoto Pharmaceutical Industry Co., Ltd.

[0092] Polyglycerol fatty acid ester B: Hexaglycerol monoisostearate (HLB value 10.8, freezing point 20°C or less), trade name "IS-601P", manufactured by Sakamoto Pharmaceutical Industry Co., Ltd.

[0093] Polyglycerol fatty acid ester C: Hexaglycerol monooleate (HLB value 11.6, freezing point 20°C or less), trade name "MO-5S", manufactured by Sakamoto Pharmaceutical Industry Co., Ltd.

[0094] Polyglycerol fatty acid ester D: Decaglyceryl monolaurate (HLB value 14.7, freezing point 20°C or less), trade name "ML-750", manufactured by Sakamoto Pharmaceutical Industry Co., Ltd.

[0095] Polyalkylene glycol fatty acid ester A: polyoxyethylene monostearate (HLB value 11.6, freezing point 35°C), trade name "NONION S-4", manufactured by NOF Corporation

[0096] (Other ingredients)

[0097] Polyglycerol fatty acid ester E: Tetraglyceryl tristearate (HLB value 4.6, freezing point 40°C or higher), trade name "TS-3S", manufactured by Sakamoto Pharmaceutical Industry Co., Ltd.

[0098] Polyglycerol fatty acid ester F: diglyceryl monoisostearate (HLB value 4.7, freezing point 20°C or less), trade name "IS-201P", manufactured by Sakamoto Pharmaceutical Industry Co., Ltd.

[0099] Sorbitan fatty acid ester: Sorbitan monopalmitate (HLB value 6.7, freezing point 45°C or higher), trade name "NONION PP-40R", manufactured by NOF Corporation

[0100] Polyglycerol fatty acid ester G: Tetraglycerol monostearate (HLB value 8.4, freezing point 40°C or higher), trade name "MS-3S", manufactured by Sakamoto Pharmaceutical Industry Co., Ltd.

[0101] Polyglycerol fatty acid ester H: Decaglyceryl tristearate (HLB value 10, freezing point 40°C or higher), trade name "TS-7S", manufactured by Sakamoto Pharmaceutical Industry Co., Ltd.

[0102] Polyglycerol fatty acid ester I: Hexaglycerol monostearate (HLB value 11.6, freezing point 40°C or higher), trade name "MS-5S", manufactured by Sakamoto Pharmaceutical Industry Co., Ltd.

[0103] Polyalkylene glycol fatty acid ester B: polyethylene glycol distearate (HLB value 19, freezing point 60°C), trade name "NONION DS-60NH", manufactured by NOF Corporation

[0104] ((B1) ingredient)

[0105] Organic acid: glutaric acid

[0106] ((B2) ingredient)

[0107] Halogen activator: trans-2,3-dibromo-2-butene-1,4-diol

[0108] ((B3) ingredient)

[0109] Amine activator: N,N,N',N'-tetrakis(2-hydroxypropyl)ethylenediamine

[0110] ((C1) component)

[0111] Solvent A: triethylene glycol monobutyl ether (BTG, melting point -48°C, boiling point 271°C)

[0112] ((C2) component)

[0113] Solvent B: triethylene glycol monoethyl ether (melting point below -44°C, boiling point 249°C), trade name "HI-MOL™", manufactured by Toho Chemical Industry Co., Ltd.

[0114] ((C3) component)

[0115] Solvent C: Hexyl Diglycol (DEH, melting point -40°C, boiling point 259°C)

[0116] Solvent D: 1,4-Butanediol (melting point 19°C, boiling point 228°C)

[0117] Solvent E: 1,6-hexanediol (melting point 42°C, boiling point 250°C)

[0118] Solvent F: 2,2-dimethyl-1,3-propanediol (melting point 128°C, boiling point 210°C)

[0119] Solvent G: 2,5-dimethyl-2,5-hexanediol (melting point 89°C, boiling point 214°C)

[0120] ((D) ingredient)

[0121] Solder powder A: Alloy composition: Sn-3.0Ag-0.5Cu, particle size distribution: 20-38μm (equivalent to IPC-J-STD-005A Type 4), melting point: 217-220°C

[0122] [Example 1]

[0123] 33% by mass of polyglycerol fatty acid ester A, 2.5% by mass of organic acid, 2.5% by mass of halogen activator, 10% by mass of amine activator, 38% by mass of solvent A, and 14% by mass of solvent B were placed in a container and mixed using a planetary mixer to obtain a flux composition.

[0124] Then, 12% by mass of the obtained flux composition and 88% by mass of the solder powder (total 100% by mass) were placed in a container and mixed with a planetary mixer to prepare a solder composition.

[0125] [Examples 2 to 9]

[0126] A solder composition was obtained in the same manner as in Example 1 except that the respective materials were blended according to the composition shown in Table 1.

[0127] [Comparative Examples 1 to 11]

[0128] A solder composition was obtained in the same manner as in Example 1 except that the respective materials were blended according to the composition shown in Table 1.

[0129] <Evaluation of Solder Composition>

[0130] The solder composition was evaluated (flux cleaning properties, printability) by the following method. The obtained results are shown in Table 1.

[0131] (1) Flux cleaning properties (liquid temperature 20°C and 60°C)

[0132] A solder composition was printed using a metal mask having a thickness of 0.2 mm and a circular pattern hole with a diameter of 6.5 mmφ, and then heated and melted at 270°C to obtain a test plate.

[0133] The resulting test plate was then immersed in a container filled with ion-exchanged water (liquid temperature 20°C) and cleaned for 5 minutes using ultrasonic waves (40kHz). The water was then replaced and washing continued for a further 5 minutes under the same conditions. The remaining liquid was then removed with an air gun and dried at room temperature for a cleaning test.

[0134] In addition, the cleaning test was performed in the same manner as above except that the liquid temperature was changed to 60°C.

[0135] The ratio of the portion where the flux component remained to the area where the residue existed before cleaning was evaluated, and the flux cleaning property was evaluated based on the remaining ratio according to the following criteria.

[0136] A: The residual ratio is less than 30%.

[0137] B: The residual ratio is 30% or more and less than 80%.

[0138] C: The residual ratio is 80% or more.

[0139] (2) Printability

[0140] Copper plates (copper, size: 50 mm × 50 mm, thickness: 0.5 mm) were prepared and polished with a polishing agent. A solder composition was printed onto the copper plates using a 0.1 mm thick metal mask with a circular pattern of holes with a diameter of 2.0 mm to produce test plates. The printed shapes on the test plates were observed under a microscope, and the printability was evaluated according to the following criteria.

[0141] A: There is no missing or blurred printing.

[0142] B: Printing omission or blurring occurred, but the occurrence area was less than 1 / 3 of the pattern. C: Printing omission or blurring occurred, and the occurrence area exceeded 1 / 3 of the pattern.

[0143]

[0144] From the results shown in Table 1, it was confirmed that the solder compositions of the present invention (Examples 1 to 9) all had good flux cleaning properties and printability.

[0145] Therefore, it was confirmed that the solder composition of the present invention has excellent cleaning properties for flux residues using an aqueous cleaning agent and also has excellent printability.

Claims

1. A flux composition comprising (A) a resin, (B) an activator, and (C) a solvent, The component (A) has an HLB value greater than 10 and a freezing point of 35°C or less, and is at least one selected from polyalkylene glycol fatty acid esters and polyglycerol fatty acid esters. The component (C) contains (C1) triethylene glycol monobutyl ether.

2. The flux composition according to claim 1, wherein The component (C) further contains (C2) triethylene glycol monoethyl ether.

3. The flux composition according to claim 1 or 2, wherein The component (B) contains (B1) an organic acid and (B3) an amine activator.

4. The flux composition according to claim 3, wherein The component (B1) is at least one selected from the group consisting of oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, fumaric acid, maleic acid, tartaric acid, and diglycolic acid. The component (B3) is at least one selected from N,N,N',N'-tetrakis(2-hydroxypropyl)ethylenediamine and N,N,N',N'-tetrakis(2-hydroxyethyl)ethylenediamine.

5. The flux composition according to claim 3, wherein The component (B) further contains (B2) a halogen-based activator.

6. The flux composition according to claim 1 or 2, wherein The component (A) is at least one selected from the group consisting of tetraglycerol monolaurate, hexaglycerol monoisostearate, hexaglycerol monooleate, decaglycerol monolaurate, and polyoxyethylene monostearate.

7. The flux composition according to claim 1 or 2, wherein The amount of the component (A) is 20% by mass or more and 50% by mass or less relative to 100% by mass of the flux composition. The amount of the component (B) is 1% by mass or more and 25% by mass or less relative to 100% by mass of the flux composition. The amount of the component (C) is not less than 10% by mass and not more than 70% by mass relative to 100% by mass of the flux composition. 8 . A solder composition comprising the flux composition according to claim 1 or 2 and (D) a solder powder. 9 . An electronic substrate comprising a soldered portion using the solder composition according to claim 8 .

10. A method for producing an electronic substrate, the method comprising: A step of applying a solder composition on a printed wiring board using a coating device; a step of disposing an electronic component on the solder composition; A reflow process of mounting the electronic component on the printed wiring board by heating in a reflow oven; and A cleaning process is performed to clean the flux residue on the electronic substrate using an aqueous cleaning agent.

Citation Information

Patent Citations

  • Preparation of entangled cocoon filament

    JP1983087330A